Implementation of integratable PDMS-based conformable microelectrode arrays using a multilayer wiring interconnect technology - Liang Guo; DeWeerth, S.P. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2009)
To meet the emerging demand of high-throughput intimate interfaces in neuroscience research and neural prosthetics, a multilayer wiring interconnect technology for implementing high-density, integratable polydimethylsiloxane (PDMS) based conformable microelectrode arrays (MEAs) is developed. This technology has two parts: first, multilayer interconnects are fabricated within PDMS, which provides the potential for implementing high-density, large-capacity PDMS-based MEAs; second, interconnects are fabricated between PDMS and a substrate material, e.g., glass or silicon, which provides the potential for directly integrating PDMS-based MEAs with silicon-based ICs to achieve an integrated system solution for neural interfacing. Preliminary muscle surface recording experiments using a connector-integrated MEA have successfully demonstrated multichannel recording capability with good device conformability to the muscle surface during contraction. Important and promising applications will be found in neural prostheses, functional electrical stimulation (FES), and basic electrophysiology research.